Mooring Measurements of Anadyr Current Nitrate, Phosphate, and Silicate Enable Updated Bering Strait Nutrient Flux Estimates. Issue 16 (15th August 2022) - Hennon, Tyler D.; Danielson, Seth L.; Woodgate, Rebecca A.; Irving, Brita; Stockwell, Dean A.; Mordy, Calvin W.
Abstract: In situ nutrient concentration data and salinity‐nutrient parameterizations established at Anadyr Strait from June 2017 to June 2018 are used to estimate monthly Pacific‐to‐Arctic fluxes of nitrate, phosphate, and silicate through Bering Strait over 1997–2019. In most months our estimates rely on measurements made from mooring‐based sensors and whole water samples, while over May–August the basis is shipboard hydrography. We find annually averaged Bering Strait fluxes of 16 ± 6, 1.5 ± 0.5, and 30 ± 11 kmol/s for nitrate, phosphate, and silicate, respectively, with inter‐annual variability ±30% of the mean. Maximum fluxes occur in April, exceeding the annual average by ∼50%, while minimum fluxes occur in December. Annually averaged fluxes estimated here are ∼50% higher than previous estimates. Significant ( p < 0.05) increasing trends in phosphate and silicate fluxes are found over 1998–2018, but not nitrate. However, it is unclear if these trend results are due to differences in draw‐down or limitations of the salinity‐nutrient parameterizations. Plain Language Summary: Nutrients flowing through Bering Strait (Pacific to Arctic) regulate the growth of Arctic plankton, which form the base of the marine food web. However, because of limited nutrient data at Bering Strait, only a few studies have attempted to estimate the size of this nutrient supply. We find that nutrients and salinity are closely related at nearby Anadyr Strait. Using those relationships and long‐term mooring observations of salinity and currents at Bering Strait, we are able to estimate Bering Strait nutrient concentrations and the amount carried through the strait into the Arctic. We find strong seasonal cycles as well as significant year‐to‐year variability. Our estimates are about 50% higher than past studies, suggesting more Pacific‐Arctic nutrient delivery than previously thought. Key Points: We use in situ and salinity‐based estimates of nutrient concentrations to estimate nutrient fluxes through Bering Strait We estimate annually averaged fluxes of 16 ± 6 (nitrate), 1.5 ± 0.5 (phosphate), and 30 ± 11 kmol/s (silicate), ∼50% larger than prior studies Bering Strait nutrient flux varies by season, with largest poleward fluxes occurring in April, and weakest fluxes occurring in December